The Persistence of American Indian Health Disparities - Jones, David S. (© American Journal of Public Health 2006, 2006)
Disparities in health status between American Indians and other groups in the United States have persisted throughout the 500 years since Europeans arrived in the Americas. Colonists, traders, missionaries, soldiers, physicians, and government officials have struggled to explain these disparities, invoking a wide range of possible causes. American Indians joined these debates, often suggesting different explanations. Europeans and Americans also struggled to respond to the disparities, sometimes working to relieve them, sometimes taking advantage of the ill health of American Indians. Economic and political interests have always affected both explanations of health disparities and responses to them, influencing which explanations were emphasized and which interventions were pursued. Tensions also appear in ongoing debates about the contributions of genetic and socioeconomic forces to the pervasive health disparities. Understanding how these economic and political forces have operated historically can explain both the persistence of the health disparities and the controversies that surround them.